2003
DOI: 10.1002/ajmg.b.20032
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of the Homer gene family and association analysis in schizophrenia

Abstract: Homer proteins are a group of proteins that regulate group 1 metabotropic glutamate receptor function. As altered glutamate function has been implicated in many neuro psychiatric disorders, particularly schizophrenia, we have screened all three known Homer genes for sequence variation for use under the candidate gene association paradigm. We found seven SNPs, including three in exons. Of these, none was non-synonymous. Allele frequencies of all the detected SNPs were estimated in DNA pools of 368 schizophrenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…The Homer protein family also assists in assembly of glutamate receptors and Ca 2 + channels in the plasma membrane (VanderVorst, 2004). Norton et al (2003) identified one SNP (Homer 1 IVS4 + 18A4G) to be associated with schizophrenia, confirmed by genotyping. Govek et al (2004) also reported absence of a Homer interacting protein, namely oligophrenin-1 (a Rho-GTPase activating protein) in a family affected with X-linked mental retardation.…”
Section: Chronic Olanzapine Treatment Sh Fatemi Et Almentioning
confidence: 73%
“…The Homer protein family also assists in assembly of glutamate receptors and Ca 2 + channels in the plasma membrane (VanderVorst, 2004). Norton et al (2003) identified one SNP (Homer 1 IVS4 + 18A4G) to be associated with schizophrenia, confirmed by genotyping. Govek et al (2004) also reported absence of a Homer interacting protein, namely oligophrenin-1 (a Rho-GTPase activating protein) in a family affected with X-linked mental retardation.…”
Section: Chronic Olanzapine Treatment Sh Fatemi Et Almentioning
confidence: 73%
“…DNA pooling allows substantial savings in genotyping costs (see, for example, references [44][45][46] ) and there have been successes using DNA pooling in the analysis of a relatively small number of markers, for example, in schizophrenia 47,48 multiple sclerosis, 49 and serum high-density lipoprotein cholesterol levels. 50,51 However, in the two cases where whole genome association has been attempted (that is, in memory 52 and mild mental impairment 53 ), the yields have been low, that is, in both cases only one locus was considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed in detail elsewhere [315], dually diagnosed schizophrenia patients typically present with more severe symptoms [308,309,[316][317][318][319], exhibit increased suicidal ideation [320,321], require more frequent hospitalizations [310,322], and experience more frequent relapses than patients without co-occurring substance abuse [323][324][325]. While analyses for polymorphisms in the Homer genes have not yet been assessed in a co-morbid population, single nucleotide polymorphisms in Homer1 have been associated with cocaine addiction [241], as well as in schizophrenia (IVS4 + 18A > G in intron 4) [326]. In addition to exhibiting increased sensitivity to the rewarding and psychomotoractivating effects of psychomotor stimulants, Homer1 KO mice exhibit a host of other behavioral abnormalities, including deficits in working memory, pre-pulse inhibition of acoustic startle, instrumental learning and habituation to a mild stressor, as well as increases in emotional reactivity to mild stressors and behavioral despair [34,172,173,307].…”
Section: Homers Addiction and Schizophrenia Co-morbiditymentioning
confidence: 99%